MTOR Repression in Response to Amino Acid Starvation Promotes ECM Degradation Through MT1‐MMP Endocytosis Arrest. Issue 17 (11th July 2021) - Colombero, Cecilia; Remy, David; Antoine‐Bally, Sandra; Macé, Anne‐Sophie; Monteiro, Pedro; ElKhatib, Nadia; Fournier, Margot; Dahmani, Ahmed; Montaudon, Elodie; Montagnac, Guillaume; Marangoni, Elisabetta; Chavrier, Philippe
Abstract: Under conditions of starvation, normal and tumor epithelial cells can rewire their metabolism toward the consumption of extracellular proteins, including extracellular matrix‐derived components as nutrient sources. The mechanism of pericellular matrix degradation by starved cells has been largely overlooked. Here it is shown that matrix degradation by breast and pancreatic tumor cells and patient‐derived xenograft explants increases by one order of magnitude upon amino acid and growth factor deprivation. In addition, it is found that collagenolysis requires the invadopodia components, TKS5, and the transmembrane metalloproteinase, MT1‐MMP, which are key to the tumor invasion program. Increased collagenolysis is controlled by mTOR repression upon nutrient depletion or pharmacological inhibition by rapamycin. The results reveal that starvation hampers clathrin‐mediated endocytosis, resulting in MT1‐MMP accumulation in arrested clathrin‐coated pits. The study uncovers a new mechanism whereby mTOR repression in starved cells leads to the repurposing of abundant plasma membrane clathrin‐coated pits into robust ECM‐degradative assemblies. Abstract : Cancer cells catabolize extracellular matrix (ECM) components to maintain growth when nutrients are depleted. This study reports that tumor cells repurpose the invadopodia‐, protease‐dependent program to elicit a massive ECM degradation mechanism, under regulation by mechanistic target of rapamycin complex 1. Nutrient scarcity blocks endocytosis of membrane type 1‐matrix metalloproteinase converting arrested clathrin‐coated pits into powerful matrix degradation units.